2004
DOI: 10.1111/j.1365-2516.2004.01005.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of haemophilia A

Abstract: Technologies in molecular biology have greatly advanced the knowledge regarding the origin of haemophilia A and the physiology of the factor VIII (FVIII) protein. A variety of different mutations in the FVIII gene have been identified and their effects on the FVIII protein described. It has been shown that the frequency of haemophilia A is due to a high mutation rate predominantly in male germ cells. A significant proportion is originating de novo in early embryogenesis from somatic mutations, a finding that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
80
2
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 47 publications
5
80
2
8
Order By: Relevance
“…[24][25][26] In the first 3000 MLOF patients reported here, the spectrum of types of F8 and F9 genetic variants we found was similar to that previously reported in hemophilia, including in a report of 829 US patients with hemophilia A or B. [1][2][3][4][5]12,[27][28][29][30] Surprisingly, despite a long history of genetic studies in hemophilia, we identified 273 previously unreported F8 and F9 DNA variants, significantly advancing our knowledge of the genetics of hemophilia. Unique novel variants continued to be identified as the first 3000 patients were enrolled, suggesting that more novel variants will be detected as the project continues.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…[24][25][26] In the first 3000 MLOF patients reported here, the spectrum of types of F8 and F9 genetic variants we found was similar to that previously reported in hemophilia, including in a report of 829 US patients with hemophilia A or B. [1][2][3][4][5]12,[27][28][29][30] Surprisingly, despite a long history of genetic studies in hemophilia, we identified 273 previously unreported F8 and F9 DNA variants, significantly advancing our knowledge of the genetics of hemophilia. Unique novel variants continued to be identified as the first 3000 patients were enrolled, suggesting that more novel variants will be detected as the project continues.…”
Section: Discussionsupporting
confidence: 73%
“…[1][2][3][4][5][27][28][29][30] Variants predicted to be gene-disrupting changes were detected predominantly in males with severe disease, as expected. SVs were more common in hemophilia A because of F8 intron 22 and intron 1 inversions, which accounted for 43% of severe male cases.…”
Section: Discussionmentioning
confidence: 65%
“…28,32 About 29% of all small deletions or insertions were found within exon 14 at one of two stretches of adenines: codons 1191-1194 (8A) and 1439-1441 (9A). 33 Overall, hot spots account for more than one-third of all point mutations in unrelated patients with HA (253/585; 43%). Exon 14 represents about one half of the coding region and encodes for the FVIII B domain, a region lacking procoagulant activity that is spliced out from the mature protein.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Point mutations, deletions, and insertions were detected in all 26 exons of the F8 gene in HA patients, causing phenotypes of variable severity characterized by complete or partial deficiency of circulating FVIII. Large deletions in the F8 gene involving one or more exons account for about 5% of all severe HA cases, 5,6 (HADB (aka HAMSTeRS) the Hemophilia A Database, http://hadb.org.uk/). The identification of a large duplication comprising one or more F8 gene exons was recently made possible following the introduction of multiplex ligation-dependent probe amplification (MLPA) technology, with an estimated occurrence of 1%.…”
Section: Introductionmentioning
confidence: 99%